Study of color reproduction features at “Nargus” LLC - Vovk, O.V.; Chebotarоva, I.B.; Polenok, D.V. (Radiotekhnika, 2022)
The features of color recreation were studied at “Nagrus” LLC. For this, the quality control process at the enterprise and the statistics of rejects and the reasons for their occurrence were analyzed; the features of the use of inks in the process of flexo printing were considered and the stages of ink preparation for printing were described. The main factors that affect the quality of products at the stage of prepress and during the process of manufacturing flexo plates were also found. The process of preparing pantone colors for printing a run was analyzed; a table of dependence of pantone deviations on various materials was created; a technique has been developed to increase the speed of paint selection and recommendations regarding its application. Factors that have the greatest influence on the quality of a flexographic plate during its manufacture were found, and a technique for the optimal choice of plates for non-absorbent materials was developed.